Young Children Give Priority to Ownership When Judging Who Should Use an Object. Issue 1 (2nd May 2013) - Neary, Karen R.; Friedman, Ori
<x xml:space="preserve">Abstract</x> This study provides evidence that children give priority to ownership when judging who should use an object. Children (N = 269) and adults (N = 154) considered disputes over objects. In disputes between a character using an object and the owner of the object, children, as young as 3 years and as old as 7 years, sided with the owner, and did so more than adults. However, children aged 4 and older disregarded owners' rights in dilemmas where these were pitted against the need to prevent harm. These findings suggest that ownership is central in children's judgments about object use and constrain developmental accounts of how children acquire an appreciation of ownership.